Structural Elucidation of a Protective B Cell Epitope on Outer Surface Protein C (OspC) of the Lyme Disease Spirochete, Borreliella burgdorferi - Michael J. Rudolph; Simon A. Davis; H. M. Emranul Haque; David D. Weis; David J. Vance; Carol Lyn Piazza; Monir Ejemel; Lisa Cavacini; Yang Wang; M. Lamine Mbow; Robert D. Gilmore; Nicholas J. Mantis (mBio, 2023)
ABSTRACT Outer surface protein C (OspC) plays a pivotal role in mediating tick-to-host transmission and infectivity of the Lyme disease spirochete, Borreliella burgdorferi. OspC is a helical-rich homodimer that interacts with tick salivary proteins, as well as components of the mammalian immune system. Several decades ago, it was shown that the OspC-specific monoclonal antibody, B5, was able to passively protect mice from experimental tick-transmitted infection by B. burgdorferi strain B31. However, B5’s epitope has never been elucidated, despite widespread interest in OspC as a possible Lyme disease vaccine antigen. Here, we report the crystal structure of B5 antigen-binding fragments (Fabs) in complex with recombinant OspC type A (OspCA). Each OspC monomer within the homodimer was bound by a single B5 Fab in a side-on orientation, with contact points along OspC’s α-helix 1 and α-helix 6, as well as interactions with the loop between α-helices 5 and 6. In addition, B5’s complementarity-determining region (CDR) H3 bridged the OspC-OspC′ homodimer interface, revealing the quaternary nature of the protective epitope. To provide insight into the molecular basis of B5 serotype specificity, we solved the crystal structures of recombinant OspC types B and K and compared them to OspCA. This study represents the first structure of a protective B cell epitope on OspC and will aid in the rational design of OspC-based vaccines and therapeutics for Lyme disease. IMPORTANCE The spirochete Borreliella burgdorferi is a causative agent of Lyme disease, the most common tickborne disease in the United States. The spirochete is transmitted to humans during the course of a tick taking a bloodmeal. After B. burgdorferi is deposited into the skin of a human host, it replicates locally and spreads systemically, often resulting in clinical manifestations involving the central nervous system, joints, and/or heart. Antibodies directed against B. burgdorferi’s outer surface protein C (OspC) are known to block tick-to-host transmission, as well as dissemination of the spirochete within a mammalian host. In this report, we reveal the first atomic structure of one such antibody in complex with OspC. Our results have implications for the design of a Lyme disease vaccine capable of interfering with multiple stages in B. burgdorferi infection.